2021
DOI: 10.1093/ofid/ofab466.502
|View full text |Cite
|
Sign up to set email alerts
|

300. Long COVID in Cancer Patients: Preponderance of Symptoms in Majority of Patients Over Long Time Period

Abstract: Background An increasing number of observational studies have reported the persistence of symptoms following recovery from acute COVID-19 disease. The long-term consequences of COVID-19 are not fully understood and there is no clear consensus on the definition of post-acute sequelae of SARS-CoV-2 infection (PASC). The reported prevalence of PASC widely varies from 10% up to 87%. The purpose of this study is to assess PASC in cancer patients following acute COVID-19 recovery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Long-COVID is associated with not only increased hospitalization for COVID-19 and complicated COVID-19 but also with an increased risk of death ( 65 ). It is observed that Long-Covid occurs in 60% of cancer patients, and it may persist up to 14 months after acute illness ( 123 ). Future investigation will guide us in deciding expectant management and surveillance imaging in these Long-COVID with cancer patients ( Figure 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long-COVID is associated with not only increased hospitalization for COVID-19 and complicated COVID-19 but also with an increased risk of death ( 65 ). It is observed that Long-Covid occurs in 60% of cancer patients, and it may persist up to 14 months after acute illness ( 123 ). Future investigation will guide us in deciding expectant management and surveillance imaging in these Long-COVID with cancer patients ( Figure 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Post-COVID-19 effects included fatigue, sleep disturbances, myalgia, gastrointestinal symptoms, dyspnea, and cough in 82%, 78%, 67%, 61%, 47%, and 46%, respectively. Of note, the persistence of these symptoms was higher in women than in men (63% vs. 37%, p = 0.036) [ 92 ]. No association was found between cancer types and long COVID-19 sequelae.…”
Section: Long Covid and Cancermentioning
confidence: 99%
“…Characteristics of patients were a median age of 64 years (range: 54–72 years), (ii) female sex (60.4%), (iii) non-Hispanic white ethnicity (76.8%), and (iv) current or former smokers (41.1%). In addition, cancer patients with long COVID had more comorbidities (OR = 4.3, [95%CI 2.9–6.2], p < 0.0001), and were more likely to be hospitalized for COVID-19 (OR = 1.3, [95%CI 1.0–1.7], p = 0.05) compared with non-cancer subjects [ 92 ]. This evidence supports the hypothesis that cancer patients are more susceptible to both COVID-19 acute and long-term complications as compared with non-cancer patients.…”
Section: Long Covid and Cancermentioning
confidence: 99%